Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
Tomar Mason, David St. Louis and ? At table; Judge Sandra Snyder playing Princess Laya 5080 E. Kings Canyon Road, Fresno